2016
DOI: 10.1002/cam4.729
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to cancer screening guidelines in Australian survivors of allogeneic blood and marrow transplantation (BMT)

Abstract: Allogeneic Blood and Marrow Transplant (BMT) survivors are at high risk of secondary cancers. Although current guidelines endorse survivors following Country‐specific general population screening recommendations to mitigate this risk, little is known about cancer screening adherence in Australian BMT survivors. We conducted a cross‐sectional survey of 441 BMT survivors who were >1 year post transplant, to explore rates of screening for secondary cancers and to identify barriers to cancer screening recommendati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 43 publications
(62 reference statements)
1
21
1
Order By: Relevance
“…We report that younger age was a predictor of cervical cancer screening, as reported in a previous study [13]. This may reflect that providers may be following the general population recommendations to perform cervical cancer screening more frequently in younger patients (every 3 years in women ages 21 to 29 years versus every 5 years in women aged 30 to 65 years).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…We report that younger age was a predictor of cervical cancer screening, as reported in a previous study [13]. This may reflect that providers may be following the general population recommendations to perform cervical cancer screening more frequently in younger patients (every 3 years in women ages 21 to 29 years versus every 5 years in women aged 30 to 65 years).…”
Section: Discussionsupporting
confidence: 80%
“…Certain cancer patients who have poor expected outcomes may need a personalized approach that takes into account their long-term prognosis and weighs the costs versus benefits of cervical cancer screening. In a study surveying allogeneic bone marrow transplant recipients in Australia more than 1 year after transplant, 63.4% of female participants reported ever receiving a Pap test since transplant [13]. In another survey female SCT survivors reported Pap testing rates of 66% and 77% for patients who underwent allogeneic and autologous SCT, respectively, at any time after SCT [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adherence to recommended guidelines for health care practices in HCT long-term survivors has received sufficient investigation to indicate that important deficits exist for half of long-term survivors (107, 137). Predictors of non-adherence include lack of knowledge of recommended surveillance tests, male gender, non-white race, younger age, autologous HCT, absence of cGVHD, poorer physical functioning, longer time since HCT, and concern about medical costs.…”
Section: Resultsmentioning
confidence: 99%
“…The few previous studies in this area have reported high rates of influenza among cancer survivors, consistent with our findings, but have lacked a cancer-free comparison group. [18][19][20][21] Hermann et al investigated outcomes among patients with a history of cancer presenting with influenza, and found no difference in mortality according to haematological or non-haematological cancer type, or activity of the cancer. 18 Our results showed considerably higher risks of hospitalisation or death among haematological cancer survivors, which could be consistent with the findings in Hermann et al if haematological cancer survivors are at increased risk of infection, but not mortality once infected, compared to non-haematological cancer survivors.…”
Section: Discussionmentioning
confidence: 99%